Different limestone particle sizes for soil acidity correction, Ca and Mg supply and corn yield - Ratke, Rafael Felipe; Pereira, Hamilton Seron; Santos_Júnior, João de Deus Gomes dos; Barbosa, Juliano Magalhães; Lopes, Liliane Oliveira (Comunicata Scientiae, 2018)
The aim of this study was to evaluate the soil acidity correction and the grain yield responses for the lime application in different granulometric particles. The limestone particle sizes incorporated into the distroferric red Oxisol were: 0.20 mm to 0.30 mm; 0.30 mm to 0.56 mm; 0.56 mm to 0.82 mm and 0.82 mm to 2.00 mm, at doses of 1.3 t ha-1; 2.6 t ha-1; 3.9 t ha-1 and 6.6 t ha-1 respectively, and a control respectively, and a control (no lime incorporation in the soil). The soil chemical characteristics pH, H+Al3+, Al3+, Ca2+ e Mg2+ were evaluated at 6 months and 18 months after the lime application. The corn yields were evaluated during the 2008/2009 and 2009/2010 crop years. Higher limestone contents and lower particle size resulted in the same effect on soil acidity correction, reducing Al3+ and increasing Ca2+ and Mg2+ in the soil when the 0.30 mm limestone was incorporated, with residual effect at 18 months. Highest corn yield was obtained when the 0.82 mm to 2.00 mm particle size was incorporated in the first crop year, when compared to the lowest limestone particle size used.